Climate Change Impacts on Lightning Density in the Operation of 150 kV High Voltage Transmission Lines in Aceh Province - Wahyu Sudrajat; Reza Putra Ramadhan; Arie Dipareza Syafei (International Journal of Science and Environment (IJSE), 2026)
Global climate change has emerged as a major issue affecting multiple sectors, including the energy sector. Rainfall variability in Aceh Province ranges from low to very high levels and occurs almost throughout the year. This study aims to identify the correlation between rainfall intensity and lightning intensity around the 150 kV high voltage overhead transmission line, as well as to assess the vulnerability level of each 150 kV transmission segment in Aceh Province. The correlation between rainfall intensity and lightning density, as a climate change factor, was analyzed using an overlay method within a Geographic Information System (GIS) framework. The vulnerability ranking of each 150 kV transmission segment was determined through a weighted assessment of external parameters lightning-related disturbance history and Isokeraunic Level (IKL). The results show that correlation between rainfall intensity and IKL (Isokeraunic Level) values for each segment shows a generally neutral relationship in five segments 150 kV High Voltage Transmission Lines in Aceh Province, where rainfall intensity tends not to have a direct effect on lightning density along the 150 kV segments. One segment, Nagan Raya–Sigli, shows a positive correlation between rainfall intensity and IKL values during the 2020–2024 period. The Langsa–Pangkalan Brandan segment is the most vulnerable to lightning, with an IKL value of 52.22%, categorized as very high.